Comparative Oviposition Site Selection in Containers by Aedes aegypti and Aedes albopictus (Diptera: Culicidae) from Florida. Issue 4 (30th March 2018) - Swan, Tom; Lounibos, L P; Nishimura, N
Abstract: Invasive container mosquito species Aedes aegypti (L.) and Ae. albopictus (Skuse) frequently co-occur in nature where they are typically segregated spatially by distinctive macrohabitat preferences that may select for different oviposition strategies. In a standard cage environment, we compared oviposition site selection by individual gravid females of these species exposed to variable numbers of water-holding cups and the presence or absence of a rugose wettable container lining. Offered plastic cups with and without lining, both species laid a significantly higher percentage of eggs in cups with lining (95.3% for Ae. aegypti, 88.4% for Ae. albopictus ), than in cups without (4.7% for Ae. aegypti, 11.6% for Ae. albopictus ). Linear regressions of container availability versus the number of lined cups colonized were similar for Ae. aegypti and Ae. albopictus . Rates of oviposition on the water surface differed by species for both cup types, with Ae. albopictus laying a higher percentage of eggs on the water surface in cups without lining (28.1% for Ae. aegypti, 51.3% for Ae. albopictus ), than in cups with (5.3% for Ae. aegypti, 2.5% for Ae. albopictus ). The more varied oviposition strategies of Ae. albopictus are interpreted in the context of its broader macrohabitat use and inferior egg desiccation resistance.